2022
DOI: 10.48550/arxiv.2205.01816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First measurement of the characteristic depletion radius of dark matter haloes from weak lensing

Matthew Fong,
Jiaxin Han,
Jun Zhang
et al.

Abstract: We use weak lensing observations to make the first measurement of the characteristic depletion radius, one of the three radii that characterize the region where matter is being depleted by growing haloes. The lenses are taken from the halo catalog produced by the extended halo-based group/cluster finder applied to DESI Legacy Imaging Surveys DR9, while the sources are extracted from the DECaLS DR8 imaging data with the F _Q pipeline. We study halo masses 12 < log(𝑀 grp [M /β„Ž]) ≀ 15.3 within redshifts 0.2 ≀ 𝑧… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 113 publications
1
0
0
Order By: Relevance
“…The splashback radii obtained from these observational data are broadly consistent with simulations, although the uncertainties in current data are quite large. Fong et al (2022) made a first attempt to measure the depletion radius using weak gravitational lensing data, and found that their results are consistent with those obtained from simulations.…”
Section: Introductionsupporting
confidence: 57%
“…The splashback radii obtained from these observational data are broadly consistent with simulations, although the uncertainties in current data are quite large. Fong et al (2022) made a first attempt to measure the depletion radius using weak gravitational lensing data, and found that their results are consistent with those obtained from simulations.…”
Section: Introductionsupporting
confidence: 57%